Features of a technique of tests of transmission oils in view of secondary structures - Сидоренко, О.Ю. (Proceedings of National Aviation University, 2004)
The developed method, as against existing, enables designers of tribosystems select the most effective Petroleum Products, with reference to conditions of their work in units of transmission.